A time-series analysis of the association between alcohol and suicide in Australia. (1st February 2022) - Miller, Mia; Anderson-Luxford, Dan; Mojica-Perez, Yvette; Sjödin, Lars; Room, Robin; Jiang, Heng
Abstract: Introduction: 800, 000 people die by suicide every year according to World Health Organisation data. Studies have shown associations between alcohol consumption and suicide, with most demonstrating that alcohol consumption increases suicide risk. However, some studies from high consumption countries show results in the opposite direction. This present study examines the association between per capita (PC) alcohol consumption and same year suicide mortality in Australia, and tests for lag effects, between 1910 and 2017. Materials and methods: Age and gender-specific autoregressive integrated moving average (ARIMA) models were used to examine associations between alcohol consumption PC and suicide mortality rates. Associations between unemployment, divorce, barbiturates access, and the Great Depression and World War II, and suicide were examined. Results: A 10% increase in PC alcohol consumption was associated with a 5% and 5.1% decrease in overall and male suicide mortality respectively in the same year. However, a 10% increase in PC alcohol consumption was associated with an 5.1% and 5.4% increase in overall and male suicide mortality respectively 12 years later. This association differed among age groups and was significant in the male population only. Unemployment, divorce, the Great Depression and WW2, and barbiturates access were significantly associated with same year suicide mortality. Discussion: Contemporaneous alcohol consumption was associated with decreased suicide mortality, but was also associated with an increased risk of suicide 12 years later. Unemployment and barbiturates access were associated with an increased risk of suicide. Interventions and policies that address chronic alcohol consumption and support the unemployed may reduce suicide mortality. Highlights: This study analyses population level data on alcohol and suicide in Australia over a 100 year period from 1910 to 2017. A 10% increase in per capita alcohol consumption was associated with a 5% decrease in overall suicide mortality in the same year. A 10% increase in per capital alcohol consumption, was also associated with a 5.1% increase in overall suicide mortality 12 years later. Alcohol consumption might be associated with decreased suicide risk in the short-term but increased risk in the longer term.